Minimalism beyond the Nurnberg funnel - Carroll, John M. 1950- (MIT Press, 1998)
Minimalism is an action- and task-oriented approach to instruction and documentation that emphasizes the importance of realistic activities and experiences for effective learning and information seeking. Since 1990, when the approach was defined in John Carroll's the Nurnberg Funnel, much work has been done to apply, refine, and broaden the minimalist approach to technical communication. This volume presents fourteen major contributions to the current theory and practice of minimalism.
"STC, Society for Technical Communication."
Keywords: Communication of technical information.; elektronické knihy; electronic books